Management power in organizations and management enterprises - Suchkov, Artem; Kulachok, Natal'ia (Management and Entrepreneurship: Trends of Development, 2018)
The urgency of the topic is due to the fact that modern entrepreneurs underestimate the scientific achievements and development of scientists. There is a lot of material associated with the organization of entrepreneurship, which would help to best organize their own business. The subject of the study is theoretical, methodological and applied aspects of the definition of the role of management in business management. Now an environment in which management becomes of special significance is formed, because the art of managing people is an important component for successful enterprise activity. Due to changing environment, management never has to be in place, which is why modern managers of all levels require rapid adaptation, new knowledge and skills that meet the requirements of the time. Purpose. The goal of the research is attraction of attention to the basis of management, namely management for the best organization and management of the enterprise in the ways of changing environment Design/methodology/approach. The basic principles of the research are the principles of causality and objectivity, system-defined and comparative methods, institutional and structural-functional approach have been used. Findings. Thus, the main stimulus that prompts an employee to work effectively is his material interest, which is realized through salary. Salary - this is part of the system of payment and incentives for work. However, rather important components of the incentive system are surcharges, bonuses and bonuses that may amount to more than 70% of the total incomes of the employee. It is very important for material incentives to take into account also psychological aspects that affect the motivation of staff. Research limitations/implications. The scientific consequence of the study is the analysis of the functions of management. Originality/value. In practice, this will help in the practical organization and management of the company. Consequently, each function is aimed at solving specific, varied and complex tasks of interaction between individual units of the organization, which require a large set of activities. The task of determining the main directions of development of production and their resource support is solved through the function of planning; the task of establishing the organizational interaction between units in the implementation of decisions and achievement of planned indicators - through the functions of the organization; task of checking performance and comparison of results with planned indicators - through the control function.